2000
DOI: 10.1128/mcb.20.9.3086-3096.2000
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of a Complex Containing Cdc45p, Replication Protein A, and Mcm2p at Replication Origins Controlled by S-Phase Cyclin-Dependent Kinases and Cdc7p-Dbf4p Kinase

Abstract: In Saccharomyces cerevisiae, replication origins are activated with characteristic timing during S phase. S-phase cyclin-dependent kinases (S-CDKs) and Cdc7p-Dbf4p kinase are required for origin activation throughout S phase. The activation of S-CDKs leads to association of Cdc45p with chromatin, raising the possibility that Cdc45p defines the assembly of a new complex at each origin. Here we show that both Cdc45p and replication protein A (RPA) bind to Mcm2p at the G 1 -S transition in an S-CDK-dependent mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
269
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 296 publications
(278 citation statements)
references
References 69 publications
(131 reference statements)
9
269
0
Order By: Relevance
“…(73) Co-immunoprecipitation experiments have shown that Cdc45 interacts with components of the pre-RC like Mcm2, but also with RPA and DNA polymerases a and e, (74) suggesting that Cdc45 may serve as a bridge between the pre-RC and the proteins required for elongation. Indeed, Cdc45 association with the origins correlates with their time of activation and requires active CDKs and DDK.…”
Section: (B) Cdc45mentioning
confidence: 99%
See 1 more Smart Citation
“…(73) Co-immunoprecipitation experiments have shown that Cdc45 interacts with components of the pre-RC like Mcm2, but also with RPA and DNA polymerases a and e, (74) suggesting that Cdc45 may serve as a bridge between the pre-RC and the proteins required for elongation. Indeed, Cdc45 association with the origins correlates with their time of activation and requires active CDKs and DDK.…”
Section: (B) Cdc45mentioning
confidence: 99%
“…Indeed, Cdc45 association with the origins correlates with their time of activation and requires active CDKs and DDK. (74,75) Its function is not limited to facilitating initiation because the controlled destruction of a degron-tagged CDC45 allele also affected elongation. (76) A recent study has suggested a role for XCdc45 as an auxiliary factor for the helicase activity of MCMs.…”
Section: (B) Cdc45mentioning
confidence: 99%
“…At least one of those functions is likely to be the loading of the Cdc45 protein onto the newly formed prereplication complex (35,47,48), although the precise mechanism of this aspect of cyclin E͞Cdk2 function remains to be elucidated.…”
Section: Cdc6 Induces Semiconservative Dna Replication In Collaboratimentioning
confidence: 99%
“…In the second step, Cdc7/Dbf4 kinase and S-phase cyclindependent kinases (S-Cdk) activate the pre-RC and trigger DNA replication by loading Cdc45 onto each origin with programmed timing (Bell and Dutta, 2002). Cdc45 facilitates assembly of the replication machinery by recruiting replication protein A and DNA polymerase a (Mimura and Takisawa, 1998;Zou and Stillman, 2000). In addition to S-Cdk and Cdc7, other factors, such as MCM10 and TopBP1, have also been shown to recruit Cdc45 (Van Hatten et al, 2002;Wohlschlegel et al, 2002).…”
Section: Introductionmentioning
confidence: 99%